Field efficacy of insecticides against chilli thrips (Scirtothrips dorsalis) and their effect on coccinellids - CHOUDHARY, JAIPAL SINGH; MONOBRULLAH, M D; KUMAR, RAKESH; RAGHAV, DUSHYANT KUMAR; SINGH, ARUN KUMAR (The Indian Journal of Agricultural Sciences, 2022)
Considering the economic significance of S. dorsalis in chilli crop, a study was carried out at the ICAR-Research Complex for Eastern Region, Farming System Research Centre for Hill and Plateau Region, Ranchi, Jharkhand during the spring season of 2019 and 2020 to find out the effective chemical molecules for managing this pest. Effectiveness of 8 modern insecticides against S. dorsalis and their effect on coccinellid predators was evaluated. Efficacy of insecticides was determined by comparing number of thrips, immature stages and adults of natural enemies, marketable yield in insecticide treated versus untreated control plots. Application of spinosad @70 g a.i./ha, Emamectin benzoate 5 sg @11 g a.i./ha, Imidacloprid 200 sl @40 g a.i./ha and Fipronil 5 sc @30 g a.i./ha were found to be effective against S. dorsalis in chilli. Other insecticides were inconsistent in effectiveness against S. dorsalis population. Fenpropathrin followed by Imidacloprid were found to cause maximum reduction and Spinosad and Emamectin benzoate caused lowest reduction of coccinellid population. Thus, based on the present study, Spinosad, Emamectin benzoate, Fipronil and Imidacloprid are recommended to manage S. dorsalis on rotational basis in chilli ecosystem.